Public Knowledge and Beliefs on Antibiotics Use and Self-Medication in Basra - Hasan Kareem Mohammed,; Majid Abdulwahab Maatook,; Rajaa Ahmed Mahmoud, (University of Thi-Qar Journal of Science, 2023)
Self-medication is described as the use of medications to address illnesses or symptoms that one has independently diagnosed, as well as the irregular or continuous use of a prescribed substance to treat persistent or recurrent illnesses or symptoms. The fundamental issue with antibiotic self-medication is the development of pathogenic resistance. Antibiotic resistance is an issue that exists today, primarily in developing nations.The main objective was to study the public's beliefs and behaviors on antibiotic use as well as self-medication with antibiotics in Basra were studied.Methods: a cross-sectional survey was conducted by using a validated questionnaire. This survey included 470 participants. (74 %) self-medicate with antibiotics. Community pharmacies (41.1%) were the most common source of antibiotics for self-medication. (74.5%) of the participants know that antibiotics are not useful for a common cold. (59.1%) of the participants have an idea of the possible harmful effects of using antibiotics. More than half of the participants 287 (61.1%) thought that self-medication with antibiotics is not an acceptable practice. (40.51%) stated as very bad practice and (32.72%) stated as bad practice.Conclusion: Most of the participants beliefs that self-medication with antibiotics is not an acceptable practice, while 74% used this practices. It is important to properly follow up the regulations and controlling the distribution of prescription medications.